Essential tremor is associated with disruption of functional connectivity in the ventral intermediate Nucleus—Motor Cortex—Cerebellum circuit. Issue 1 (15th October 2015) - Fang, Weidong; Chen, Huiyue; Wang, Hansheng; Zhang, Han; Puneet, Munankami; Liu, Mengqi; Lv, Fajin; Luo, Tianyou; Cheng, Oumei; Wang, Xuefeng; Lu, Xiurong
Abstract: The clinical benefits of targeting the ventral intermediate nucleus (VIM) for the treatment of tremors in essential tremor (ET) patients suggest that the VIM is a key hub in the network of tremor generation and propagation and that the VIM can be considered as a seed region to study the tremor network. However, little is known about the central tremor network in ET patients. Twenty‐six ET patients and 26 matched healthy controls (HCs) were included in this study. After considering structural and head‐motion factors and establishing the accuracy of our seed region, a VIM seed‐based functional connectivity (FC) analysis of resting‐state functional magnetic resonance imaging (RS‐fMRI) data was performed to characterize the VIM FC network in ET patients. We found that ET patients and HCs shared a similar VIM FC network that was generally consistent with the VIM anatomical connectivity network inferred from normal nonhuman primates and healthy humans. Compared with HCs, ET patients displayed VIM‐related FC changes, primarily within the VIM‐motor cortex (MC)‐cerebellum (CBLM) circuit, which included decreased FC in the CBLM and increased FC in the MC. Importantly, tremor severity correlated with these FC changes. These findings provide the first evidence that the pathological tremors observed in ET patients might be based on a physiologically pre‐existing VIM ‐ MC ‐ CBLM network and that disruption of FC in this physiological network is associated with ET. Further, these findings demonstrate a potential approach for elucidating the neural network mechanisms underlying this disease. Hum Brain Mapp 37:165–178, 2016 . ©2015 Wiley Periodicals, Inc.